LncRNA FGD5-AS1 drives the malignant development of gastric cancer by negatively interacting with FZD3 - Feng, Limin; Zheng, Hui; Zhang, Huaping; Cao, Mingxiao; Zhou, Hua (Polish Journal of Pathology, 2022)
We aimed to detect the expression pattern of long non-coding RNA (lncRNA) FGD5-AS1 in gastric cancer (GC) samples and its impact on driving the development of GC. FGD5-AS1 levels in 66 cases of GC tissues and paracancerous ones were detected. Its influences on clinical features and prognosis in GC patients were analyzed. In AGS and SGC-7901 cells with FGD5-AS1 knockdown, phenotype changes were assessed through cell counting kit-8 (CCK-8), Transwell and wound healing assay. The downstream target of FGD5-AS1 was searched by a bioinformatics tool and confirmed by dual-luciferase reporter assay. Their interaction in regulating the malignant development of GC was finally explored. FGD5-AS1 was upregulated in GC tissues compared to paracancerous ones. GC patients expressing a high level of FGD5-AS1 had higher risk of lymphatic metastasis or distant metastasis and worse prognosis than those with a low level. Knockdown of FGD5-AS1 weakened proliferative and metastatic abilities in AGS and SGC-7901 cells. FZD3 was the downstream target of FGD5-AS1. Protein levels of FZD3 and FZD5 were upregulated, while b-catenin, TGF-b and MMP9 were downregulated in GC cells with FGD5-AS1 knockdown. Knockdown of FZD3 abolished the regulatory effects of FGD5-AS1 on malignant phenotypes of GC cells. FGD5-AS1 is upregulated in GC samples, which is linked to metastasis and prognosis in GC. It drives proliferative and metastatic abilities in GC cells via negatively interacting with FZD3.